Preserving traditional Balinese architecture: exploring the relevance of undagi’s indigenous knowledge in post-pandemic interior design - I Kadek Dwi Noorwatha; Imam Santosa (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
This research is focused on exploring the relevance of undagi’s indigenous knowledge implemented on post-pandemic interior design as a recommendation for preserving traditional Balinese architecture in the modern era. As UNESCO promoted safeguarding the "Intangible Cultural Heritage" in 2003, all designers must strengthen the cultural side in still relevant designs for the modern era. In Bali, undagi’s (traditional architect) existence declined in the modern era. Undagi’s indigenous knowledge is the basis for the architectural development of traditional Balinese houses (umah) for designing tourism facilities as research objects. This research is a desk study with a critical analytical approach that qualitatively conducts a comparative study between indigenous knowledge and post-pandemic interior design recommendations with two stages of research—in the first stage, critically analyzing post-pandemic interior design recommendations by previous researchers with a systemic literature review. In the second stage, exploring undagi’s indigenous knowledge consists of explicit and tacit knowledge. The result of the two stages is the formulation of the relevance of undagi’s indigenous knowledge in post-pandemic interior design in Bali. The study results show that the undagi’s indigenous knowledge has relevance, which aligns with the recommendations for post-pandemic interior design criteria by previous researchers. This relevance is closely relevant, and several relevant values require development and interpretation to have interconnectivity between modern and traditional values. This process of interconnectivity must prioritize the principle of preserving traditional Balinese architecture in the modern era.